Development of an optimized febuxostat self-nanoemulsified loaded transdermal film: in-vitro, ex-vivo and in-vivo evaluation. (15th March 2020) - Alhakamy, Nabil A.; Fahmy, Usama A.; Ahmed, Osama A. A.; Almohammadi, Enas A.; Alotaibi, Shahad A.; Aljohani, Raghad A.; Alharbi, Waleed S.; Alfaleh, Mohamed A.; Alfaifi, Mohammad Y.
Abstract: Febuxostat (FBX) is used to treat gout and chronic hyperuricemia. However, its bioavailability is moderate (49%) as a result of low solubility and first-pass metabolism. Therefore, the aim of our study is to improve FBX bioavailability by enhancement its solubility using self-nanoemulsifying drug delivery system (SNEDDS) technique in the form of transdermal film to avoid hepatic metabolism. To accomplish this goal, Eight SNEDDS formulae were prepared according to a three-factor, two-level D-Optimal mixture design to evaluate the effect of different ratios of the Lemon oil (X1), the surfactant Tween-20 (X2), and the co-surfactant PEG-400 (X3) on the globule size in order to reach smallest globular size. Results revealed that SNEDDS globule size ranged from 177 to 454 nm. The optimized formula consisted of 20% oil, 40% surfactant and 40% co-surfactant. Diffusion study showed improved enhancement in skin permeation that was confirmed by imaging using fluorescence microscope. In vivo plasma data showed significant ( p < 0.05) difference in FBX plasma levels and pharmacokinetic parameters when compared with raw FBX loaded film. In conclusion, FBX-SNEDDS loaded transdermal film could be a successful way to improve solubility and skin permeability that would lead to improvement in patient's compliance.